Pengaruh Model Belajar Murder Terhadap Penguasaan Peserta Didik Di MTs PP Tunas Harapan Tembilahan - Ein Maria Olfa (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2020)
The success of a teacher in teaching is not only determined by learning strategies and methods. The most supportive success thing or failure of the learning process is a lot of determined by students' emotions. The teacher is one who determines and leads the learner's emotions towards positive so that they have to accept learning already. Then, the learning process is considered successful to lead students in achieving learning objectives, we need an effective way of learning. One effective way is to use MURDER, MURDER is an abbreviation of Mood, Understand, Recall, Digest, Expand, and Review. The purpose of this study was to determine the Effect of Learning Implementation of MURDER (Mood, Understand, Recall, Digest, Expand, Review) Against Student Mastery in Moral Aqeedah in Tsanawiyah Tsanawiyah PPTH Tembilahan Madrasah. This research is field research (field research), using a quantitative approach. The subjects in this study were the teachers of the moral creed and students in the Tsanawiyah PPTH Madrasah Tembilahan, Tembilahan District, Indragiri Hilir Regency. The results of the study, obtained from the implementation of the MURDER learning, the results that t_o is greater than t table or 2.110 <8.37> 2.898 then the null hypothesis proposed is rejected, meaning that there is a significant influence of MURDER learning (Mood, Understand, Recall, Digest, Expand, Review) on the mastery of students in learning